Language Planning and Policy Proposal - Murodova Iroda Alisher qizi (Zien Journals, 2022)
As the world has become more globalized, English has become the “world language”(Brutt Giffle,2002). English has been gaining its high status since it is a language of communication and exchanging ideas in the world, therefore, everyone who is involved in education, business and commerce is supposed to know the language at a certain level. Mufwene(2002) emphasizes that “English is the first foreign language in many Asian countries and is seen as the key determinant of economic survival for countries in a changing socioeconomic ecology.
Keywords: determinant; become; globalized; language